Perjanjian Kredit Bank dalam Hal Surat Kuasa Membebankan Hak Tanggungan Tidak Diikuti dengan Akta Pemberian Hak Tanggungan - Ni Made Seri Wahyuni Dewi; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2022)
Deed of Imposition of Mortgage which is processed before a Notary/PPAT and attended by both parties, namely the debtor and creditor. If one of them is unable to attend, the party who is unable to attend will be issued an SKMHT which has a period of one month for land that has been registered and three months for land that is not registered in accordance with the provisions of Article 15 paragraphs (3) and (4) of the UUHT, apart from The validity period of the SKMHT is also affected by the existence of other processes such as: inheritance, roya and rights conventions. This study aims to disclose the Bank's credit agreement in the event that the power of attorney to impose mortgage rights is not followed by the fact of granting mortgage rights. This study uses research methods in the form of normative research with a normative juridical approach, namely analyzing the norms or rules that apply. Primary data and secondary data are used in this study. Data were analyzed using qualitative methods. The results of the study show that the position of the bank as a creditor if the SKMHT is not made APHT is a concurrent creditor which means the bank does not have special rights as contained in the Civil Code, if the debtor is in default while the creditor is a concurrent creditor, the handling of civil cases is generally.